A comprehensive evaluation of the accuracy of CBCT and deformable registration based dose calculation in lung proton therapy. (6th January 2017) - Veiga, Catarina; Janssens, Guillaume; Baudier, Thomas; Hotoiu, Lucian; Brousmiche, Sebastien; McClelland, Jamie; Teng, Ching-Ling; Yin, Lingshu; Royle, Gary; Teo, Boon-Keng Kevin
Abstract: The uncertainties in water equivalent thickness (WET) and accuracy of dose estimation using a virtual CT (vCT), generated from deforming the planning CT (pCT) onto the daily cone-beam CT (CBCT), were comprehensively evaluated in the context of lung malignancies and passive scattering proton therapy. The validation methodology utilized multiple CBCT datasets to generate the vCTs of twenty lung cancer patients. A correction step was applied to the vCTs to account for anatomical modifications that could not be modeled by deformation alone. The CBCT datasets included a regular CBCT (rCBCT) and synthetic CBCTs created from the rCBCT and rescan CT (rCT), which minimized the variation in setup between the vCT and the gold-standard image (i.e., rCT). The uncertainty in WET was defined as the voxelwise difference in WET between vCT and rCT, and calculated in 3D (planning target volume, PTV) and 2D (distal and proximal surfaces). The uncertainty in WET based dose warping was defined as the difference between the warped dose and a forward dose recalculation on the rCT. The overall root mean square (RMS) uncertainty in WET was 3.6 ± 1.8, 2.2 ± 1.4 and 3.3 ± 1.8 mm for the distal surface, proximal surface and PTV, respectively. For the warped dose, the RMS uncertainty of the voxelwise dose difference was 6% ± 2% of the maximum dose (%mD), using a 20% cut-off. The rCBCT resulted in higher uncertainties due to setup variability with the rCT; the uncertainties reported with the two synthetic CBCTs were similar. The vCT followed by a correction step was found to be an accurate alternative to rCT.